Zero trust framework for protecting federal networks and cloud services - Sudheer Kotilingala (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2025)
There has been a rapid uptake of cloud technologies in public sectors due to increased efficiency across operations while increasing the complexity of cyber threats. This paper analyses the original Zero Trust Architecture (ZTA) concept as a security concept applicable to federal networks and cloud services protection. It mainly involves linking ZTA principles with FedRAMP regulations and insists on constant validation, minimisation of rights, and breach presumption. The study outlines guidelines for ZTA implementations for compliance and readiness in the cloud environments.